Rockfall hazard in Greece. - Saroglou, H. (Bulletin of the Geological Society of Greece, 2013)
The geological structure of Greece (frequent occurrence of rock formations, existence of faults and fracturing of rocks), the steep topography and mountainous terrain as well as its high seismicity, creates a significant rockfall hazard. During the last decades, rockfalls in Greece are becoming a frequent phenomenon due to the increase of intense rainfall events but also due to the extension of human activities in mountainous areas. The paper presents rockfall hazard in Greece trough an inventory of rockfalls and investigates the correlation of specific factors, namely: a) triggering mechanism (rainfall, seismicity), b) slope angle, c) lithology, d) fault presence, e) block size in the probability of occurrence of these, based on a statistical approach. The time and space frequency of the events is also investigated. Finally, the impact of the events on human and infrastructures (transportation infrastructure, inhabited areas, archaeological sites) is discussed.